TRANSLATING ANIMATION BY EKI N. F., DEDDY OTARA, AND ZULFA ASLIHA ENTITLED “EYANG HABIBIE” ADIT AND SOPO JARWO - Cahyana, Lanang Mahardhika; Setiawan, Kristianto; Sudja’ie, Mimien Aminah (Jurnal Vokasia, 2021)
This article is entitled Translating Animation by Eki N. F., Deddy Otara, and Zulfa Asliha entitled “Eyang Habibie” Adit Sopo Jarwo. The purpose of translates Adit Sopo Jarwo’s animation"Eyang Habibie" into English because it presents many cultures in Indonesia and the important aspect of this animation movie is how they respect each other’s differences in their cultures. Therefore, this animation is an interesting object to be translated so as to be enjoyed by foreign viewers. In the process of translating there were several obstacles which included, translator’s limited knowledge of vocabulary in the target language and source language, difficulty in determiningthe equivalent of words in the Target language to be communicative, and difficulty in using "aegisub" subtitle application to equate what the characters say with the subtitles. Anyway, they were solved by using a dictionary to find out words/vocabularies that were not understood, searching the equivalent in the Target Language and then consulting with the proofreader to determining the communicative equivalent then using it in the Target language and also learning about the features available in subtitle application called "aegisub".